Multi-fractal Analysis for Riemann Serie and Mandelbrot Binomial Measure with (min,+)-Wavelets. - Gondran, Michel; Kenoufi, Abdelouahab; Lehner, Thierry (Trends in Computational and Applied Mathematics, 2016)
One introduces first the so-called (min, +)-wavelets which are lower and upper hulls build from (min, +) analysis in order to perform multi-fractal analysis. In a second step it is applied to functions such as the Riemann serie and binomial Mandelbrot measure for numerical computations of their singularities spectrum, and comparisons with well-known theoretical and to WTMM method results.